Liglugten af den moderne Civilisation? Moralstatistiske perspektiver på selvmord i 1800-tallets Danmark - Andersen, Lars (Slagmark - Tidsskrift for idéhistorie, 2020)
English summary This article investigates the impact of moral statistics on suicide in Denmark in the 19. century. Championed as a new European social science, moral statistics was able to reveal statistical regularity on social and moral issues – such as suicide. Statistics proved, firstly, that Denmark experienced one of the highest suicide rates in Europe. Secondly, as demonstrated in 1846 by the Danish physician C. J. Kayser, statistics uncovered that suicides over time occurred regularly in the case of frequency, gender distribution, method of self-killing etc.. This new knowledge encouraged Danish statisticians and physicians to look for societal causes rather than the former theological focus on individual sin. The statistical representations of suicide paved the way for two different interpretations of suicide in the second half of the 19. century, one of which linked suicide rates to the evils of modernisation and secularisation of society, emphasizing drunkenness, alcoholism, and moral decline as causes of suicide. Another, less prevalent, explanation stressed the social and economic inequality of industrialisation as the cause of rising suicide rates. ‘The moral explanation’ prevailed and the official statistical reports as well as newspaper articles was clearly affected by the idea that the rising suicide rates of the 19. century reflected an attack on core values of bourgeois society; moral, sobriety and religion. This way suicide statistics was embedded in a broader social representation reflecting a fear of breakdown of traditional values in modern society.